Respon Peserta Didik pada Pembelajaran Moderasi Beragama Berbantu Media Educard Literasi di Madrasah Ibtidaiyah - Rofiah, Siti (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2024)
This study aims to examine students’ responses to religious moderation learning assisted by educard literacy media in an islamic elementary school/ the research method employed is quantitative research with survey research design. The study sample consist of fourth-grade students at MI Islamiyah AL Wathaniyah Bareng Jombang. Data collection was carried out using questionnaires administered to the students. Data analysis was conducted using descriptive statistical techniques. The results indicate that students’ responses to religious moderation learning assisted by educard literacy media tend to be positive in three aspects cognition at 81,5%, affective aspect at 80,65 %, and conative aspect at 82,5%, all categorized as strong, with the majority of students showing high interest and goodunderstanding of the learning materials. These findings suggest that the use of educard literacy media can effectively enhance students engagement and understanding in religious moderation learning at the Islamic elementary level. Keywords : students’ response, religious moderation learning, educard literacy